Bionic structures for optimizing the design of stealth materials. Issue 8 (13th February 2023) - Xu, Zhengkang; Li, Jiatong; Li, Jinzhe; Du, Jiani; Li, Tian; Zeng, Weigui; Qiu, Junhai; Meng, Fanbin
Abstract : Overview of bionic structure in performance optimization and structural design. Abstract : Traditional microwave absorbing materials (MAMs) have exposed more and more problems in multi-spectrum detection and a harsh service environment, which hinder their further application. Bionic materials and structures have attracted more and more attention from researchers in the field of stealth materials due to their excellent properties, such as high strength and high conductivity, along with easy access to scale adjustability and structural design. By introducing the concept of bionics into their structural design and material design, we can obtain highly efficient stealth materials with multiple properties. In addition, the concept of multispectral stealth is furthered by comparing the difference in the principle and methods of achievement between radar stealth and infrared stealth. This paper fundamentally summarizes the research status of bionic structure design ideas in stealth materials, analyzing the structure–activity relationship between the structural size effect and electromagnetic characteristics from low order to high order. Then, the design ideas and universal strategies of typical bionic structures are summarised and an idea for the integrated design of radar absorption compatible with infrared stealth is put forward. This will provide profound insights for the application of biomimetic stealth materials and the future development of intelligent-response and dynamically adjustable materials.